Batad sa paang palay - Acedillo, Vic; Alajar, Gina; Buencamino, Noni; Galura, Alchris; Garcia, Benji; Cinemalaya ([Pace of production not identified] Cinemalaya, 2006)
A 14-year old Batad Boy, a high school dropout, is forced to sell produce in the Banawe market to augment the family income while his father pursues the philantrophic mission of repairing the rice terraces of adjoining Ifugao villages. Exposed to Western modernization in Banawe, the boy obsesses with owning a pair of rubber shoes that he does not really need. In pursuit of his dream sneakers, he takes on all odd jobs imaginable and ultimately becomes a tour guide. During one of his tours, he barters his guide fee for a pair of shoes which are, however, too big for him. Upon possessing the long-desired rubber shoes, he attempts to leave his Ifugao roots and chase big city dreams.--Cinemalaya 2006
"Summary taken from https://www.imdb.com/title/tt0843469/plotsummary?ref_=tt_ov_pl
Produced by Vic Adecillo, Flor Salanga; music by Belinda Salazar; cinematography by Ruben dela Cruz.
Gina Alajar, Noni Buencamino, Alchris Galura.
DVD
In Tagalog
Keywords: Drama